Influence of Microwaves on the Thermal Conditions of a "Polymer–Semiconductor–Composite" System; Journal of Engineering Physics and Thermophysics; Vol. 88, iss. 6 - Kuznetsov G. V. Geny Vladimirovich (2015, 2015)
Title screen